MONTASE MEWUJUDKAN FANTASI DALAM FILM POHON PENGHUJAN - Rohma, Naafi Nur; Ali, Matius (Capture : Jurnal Seni Media Rekam, 2016)
The research titled Montage Realizing Fantasy in the Rain Tree Film (MontaseMewujudkan Fantasi dalam Film Pohon Penghujan)uses qualitative research methods with a formalist esthetic approach and Eisenstein's montage theory. The problem in this research is how the montage manifests the fantasy in the RainTree film?The study in this study focuses on the montage, thus giving meaning in the fantasy film of the Rainbows. The analysis used to dissect the problems used Eisenstein montage theory, namely metric,rhythmic,tonal,overtonal,and intellectual.The results obtained in the research shows a way of fantasy creation,that is,there are some Lacan fantasy scenes,the way the subject is eagerly read through the Eisenstein montage. Through the montage of Eisenstein can be seen the essence of each shot is displayed and the formation of how the characters in the film RainTree knows his passion and shapes his desire through a series of montage.Keywords: Fantasy,Montage,RainTree.